Analisis Tingkat Postur Kerja Dan Musculoskeletal Disorders pada Pekerja di Pabrik Roti Latansa Gontor - Basri, Ani Asriani; Arifah, Dian Afif (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2020)
The La Tansa bakery industry is a formal industrial sector that makes bread, some process activities are still repeated manually. This condition will cause the prevalence of MSD complaints because the worker's body position is bent. The purpose of this study was to assess the level of risk of injury using the Quick Exposure Check (QEC) questionnaire and to assess complaints about the impact of this awkward posture using the Nordic Body Map (NBM) questionnaire. This type of research was descriptively carried out at the Latansa Bread Factory, Gontor Ponorogo in May 2020 with a total of 9 respondents. The research results will be analyzed using the Excel program. Based on the results of research on the distribution of questionnaires conducted by researchers and the workers themselves, it shows that the level of risk of injury to 7 out of 9 workers is at the level of 72.8% - 82.7%, which means that research and changes must be carried out as soon as possible. The results of MSD's complaint assessment among workers showed that all were categorized as having moderate complaints. The advice given to the Latansa Bread Factory is to design a chair and table for workers so as to minimize the risk of injury and create effective, safe, comfortable and efficient working condition.